ANALISA DIGITAL MARKETING SEKTOR PERBANKAN: PERBANDINGAN APLIKASI MOBILE BANKING LIVIN’ BY MANDIRI DAN MYBCA DALAM MEMAKSIMALKAN POTENSI PASAR DIGITAL - Chanda Vedalla Putra; Ng Thian Way; Ricky Ricky; Shelby Esfandiany; Eryc Eryc (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
In this modern era, the need for people to conduct financial transactions remotely has become very common. Recognizing this phenomenon, banks in Indonesia, including BCA and Mandiri, have developed mobile banking applications to meet this need. To increase public awareness of these applications, the banks have implemented digital marketing strategies to maximize the potential of the digital market that can be reached. The research conducted found that BCA and Mandiri banks have been optimizing their digital marketing efforts, although some sectors of digital marketing can still be improved to broaden the reach of customers who are aware of these applications